Evolution of the revenue/ expenditure structure and passenger cost coverage ratio of regular passenger transport between 2007 and 2022 - Ács, Balázs; Kövesdi, István (Public Finance Quarterly, 2024)
This article presents a general methodology for aggregating the actual costs and revenues of public transport in Hungary, which allows to calculate a realistic passenger (user) cost coverage ratio for the main players in the domestic market (MÁV-Volán Group, GYSEV, BKK). After an international perspective and a presentation of the specificities of the domestic market, it is concluded that the cost coverage ratio for fixed rail transport is significantly lower than for public transport services on road. The main reason for this is that fixed rail infrastructure is expensive to develop and operate and is mainly used by public passenger transport. The ridership ratio is significantly reduced by significant investments, and this has been analysed both on a time series and average basis. We present the timetable, tariff changes and major investments that have had an impact on ridership rates, typically only to a small extent. Our analysis is financially oriented and only touches on positive externalities, social benefits and the general government balance